Cardiovascular risk factors in children on dialysis: an update - Querfeld, Uwe; Schaefer, Franz (Pediatric nephrology, 2020)
Cardiovascular disease (CVD) is a life-limiting comorbidity in patients with chronic kidney disease (CKD). In childhood, imaging studies have demonstrated early phenotypic characteristics including increases in left ventricular mass, carotid artery intima-media thickness, and pulse wave velocity, which occur even in young children with early stages of CKD. Vascular calcifications are the signature of an advanced phenotype and are mainly found in adolescents and young adults treated with dialysis. Association studies have provided valuable information regarding the significance of a multitude of risk factors in promoting CVD in children with CKD by using intermediate endpoints of measurements of surrogate parameters of CVD. Dialysis aggravates pre-existing risk factors and accelerates the progression of CVD with additional dialysis-related risk factors. Coronary artery calcifications in children and young adults with CKD accumulate in a time-dependent manner on dialysis. Identification of risk factors has led to improved understanding of principal mechanisms of CKD-induced damage to the cardiovascular system. Treatment strategies include assessment and monitoring of individual risk factor load, optimization of treatment of modifiable risk factors, and intensified hemodialysis if early transplantation is not possible.
Published: 31 Oktober 2018
Gesehen am 18.05.2020